Effect of new-onset atrial fibrillation on cause-specific late mortality after coronary artery bypass grafting surgery. (21st February 2018) - Schwann, Thomas A; Al-Shaar, Laila; Engoren, Milo C; Bonnell, Mark R; Goodwin, Matthew; Schwann, Alexandra N; Habib, Robert H
Abstract: OBJECTIVES: Postoperative atrial fibrillation (POAF) is a common complication after coronary artery bypass grafting. Although transient, POAF is linked to increased late mortality. We hypothesized that POAF increases late cerebrovascular (CeV) and composite cerebrovascular/cardiovascular/vascular (CV* = CeV + CV + Other-V) but not non-cardiovascular (Non-CV) mortality. METHODS: We analysed 8807 non-salvage coronary artery bypass grafting patients (1994–2011). Fifteen-year and time-segmented (early, 0–1 year; intermediate, 1–6 years and late, 6–15 years) all-cause and cause-specific mortality were compared for POAF versus No-POAF patients. Corresponding POAF versus No-POAF adjusted hazard ratios [AHRs (95% confidence interval, CI)] were derived using the competing risk Cox regression. RESULTS: POAF occurred in 1992 (23%) patients. Complications other than POAF occurred in 1875 (21%) patients but were more frequent among POAF patients (31% vs 18%; P  < 0.001). Overall mean follow-up was 9 ± 4 years. POAF patients had a higher 15-year unadjusted mortality (53% vs 39%; P  < 0.001) and were consequently associated with higher adjusted all-cause [AHR (95% CI) = 1.23 (1.14–1.33)] and composite cardiovascular [CV*: AHR (95% CI) = 1.15 (1.02–1.30)] mortality. The trends towards a higher 15-year CeV [AHR (95% CI) = 1.34 (0.94–1.91)] and Non-CV [AHR (95% CI) = 1.12 (0.99–1.26)] mortality were not significant. Time-segmented analyses showed that (i) POAF increased all-cause mortality early, and this persisted in the intermediate and late periods and (ii) CeV [AHR (95% CI) = 2.14 (1.14–4.04)] and CV* [AHR (95% CI) = 1.31 (1.06–1.62)] mortality rates were increased in the intermediate but not in the early or late periods. Non-CV mortality was similar in POAF and No-POAF for all time intervals. These findings were corroborated in propensity-matched sub-cohorts and in sensitivity analyses in patients free of any other complication. CONCLUSIONS: POAF is associated with worse long-term survival principally driven by increased intermediate-term cerebrovascular and cardiovascular mortality, while Non-CV mortality was similar.